ANALYSIS OF NON-PERFORMING LOAN CREDIT RECOVERY CASE STUDY: PT. BANK MANDIRI (PERSERO) TBK. â REGIONAL SPECIAL ASSET MANAGEMENT BANDUNG - Banu Adji, Ardhita
It has become a common view that the high ratio of non-performing loans (NPLs) in a bank will affect the income of the bank because income must be reserved for losses where the source is from profits. Portfolio of loans problem in West Java continues to increase in the period under study while the average recovery obtained in percentage has proven to be declining, based on this it is necessary to research to find the best recovery method with the smallest risk so that expected to solve existing problems. This research step starts with processing data recovery performance comparing from the period June 2016 to June 2019 (3 years), grouping them into account recovery strategies used by Bank Mandiri (Billing, Payment with Interest & Fine Relief, Collateral Liquidation & Auction, Restructuring, and Subrogation & Bankruptcy) and find out which account strategy produces the greatest recovery performance with the parameters of total recovery, average recovery, and sustainability. Risk analysis was also carried out in this study with qualitative data obtained based on interviews with experienced employees at the management level (Manager-Vice President) at PT. Bank Mandiri (Persero) Tbk. - Regional Special Asset Management Bandung. To obtain more objective decision, author use decision-making tools Super Decision using Analytical Hierarchy Process (AHP) methodology this tools extended the interconnected analysis between each criterion and its relation to all possible alternatives. The results of this study indicate that the method of credit repayment that produces the most with a contribution during the analysis period of 32% is Collateral Liquidation & Auction, followed by Restructuring by 26%. However, based on the results of interviews found that the method of return with the highest risk is Collateral Liquidation & Auction (the worst among other recovery methods) and causes to increase handling costs (trials and accommodation), while the smallest risk is Restructuring. The result of analysis using AHP software super decisions version 2.10 also show that the highest weight account strategy compared to all alternative is restructuring Based on that facts, it is recommended to have the tools to take early steps to handle loan problems with the aim of restructuring actions so that the efforts to recover credit can be carried out early with the smallest possible risk but still producing good recovery performance.